Using the Eisenhower Matrix to Identify Open Government Data Parameter Towards Information Disclosure in Indonesia - Herma Adis; Catur Apriono (Buletin Pos dan Telekomunikasi, 2024)
The openness of government data is considered essential and is an influential innovation in society to prevent corruption by increasing the transparency of information and data. One of the drivers for the emergence of Open Government Data (OGD) is the Industrial Revolution 4.0 era, which has influenced all aspects of life with all technological advances. Society needs open information to support and monitor the running of Government. However, it still needs to be determined whether the published OGD data is actual data or only data presented to cancel obligations to protect certain powers. From here, the author wants to conduct a study on OGD parameters using the Eisenhower matrix after reviewing several experts in the telecommunications sector as a basis for identifying parameters for the openness of information and government data in Indonesia. From the results of the analysis that we have carried out, it is found that government support is the highest parameter, followed by other parameters, namely policy, data transparency in the OGD portal, and the participation of citizens as the most crucial support in supporting the implementation of quality and quality OGD data publication in Indonesia. So, the final aim of this study is to provide a future view for all policies that will be made by the Government related to OGD to include all parameters that support data transparency that can be used optimally by the general public so that actual data publication is achieved that does not protect authority or specific power.